Improving the Effectiveness of Islamic Religious Education Learning Through Transformational Leadership, Implementation of Cooperative Learning Models, and Learning Motivation - Hermawan, Andi; Alhamdan, Latif Sufi; Kholili, Ahmad (Jurnal Inovasi Pendidikan MH Thamrin, 2025)
The composed combination includes human elements, materials, facilities, equipment and procedures to change student behavior in a positive and better direction with the potential and differences that students have to achieve predetermined learning goals, this is what is meant by learning effectiveness . Learning effectiveness is an important element related to achieving educational goals. Religious subjects are learning that is always a benchmark for behavior and attitudes. It is known that the effectiveness of learning Islamic Religious Education subjects at private vocational schools in Bogor Regency is not as expected. Therefore, research is needed to obtain information on variables related to increasing learning effectiveness. The aim of this research is to carry out strategies and ways to increase learning effectiveness by conducting research on the influence between the implementation variables of the cooperative learning model, transformational leadership and learning motivation. This research uses the path analysis method to determine the influence between the variables studied and the SITOREM method for indicator analysis to obtain strategies and ways to increase learning effectiveness.